Invariance properties and conservation laws of the nonlinear damped wave equation with power law nonlinearities - Usamah S. Al Ali; Ashfaque H. Bokhari; A.H. Kara; F.D. Zaman (Results in Physics, 2017)
Nonlinear evolution equations represent some of the most fundamental processes in both physics as well engineering. Considering this, we analyze and classify the three dimensional wave equation with a power law nonlinearity in presence of damping and external force terms. In view of the significance of conservation laws in physics, a study of the invariance properties is presented and conservation laws are constructed and classified. An illustrative case of a symmetry reduction in one special case is presented. Keywords: Power law non-linearity, Diffusion, Damped wave, Conservation laws